2022
DOI: 10.20960/nh.03992
|View full text |Cite
|
Sign up to set email alerts
|

The effect of omega-3 fatty acid supplementation on weight loss and cognitive function in overweight or obese individuals on weight-loss diet

Abstract: The effect of omega-3 fatty acid supplementation on weight loss and cognitive function in overweight or obese individuals on weight-loss dietEl efecto de la suplementación con ácidos grasos omega-3 sobre la pérdida de peso y las funciones cognitivas en personas con sobrepeso u obesidad en dieta para adelgazar

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…In addition, it is a challenge to sustain such low-calorie diets over an extended period [ 26 ]. Studies using different dietary interventions, including increases in w –3 polyunsaturated fatty acids (PUFA) but not protein intake, have been conducted to decrease visceral fat mass and improve abdominal obesity [ 27 , 28 ]. Intermittent fasting and ketogenic diets have also been considered to reduce abdominal obesity [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is a challenge to sustain such low-calorie diets over an extended period [ 26 ]. Studies using different dietary interventions, including increases in w –3 polyunsaturated fatty acids (PUFA) but not protein intake, have been conducted to decrease visceral fat mass and improve abdominal obesity [ 27 , 28 ]. Intermittent fasting and ketogenic diets have also been considered to reduce abdominal obesity [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A negative association between EPA and fat mass was found in our study. Previous studies reported that positive effects of PUFAs on body fat mass loss may be associated with a modulation of lipid metabolism and muscle anabolism in obese subjects [ 61 , 62 ]. More studies in runners are necessary to investigate this association.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also found that C18:3 n-3 in the erythrocyte membrane n-3 fatty acid profile was significantly different between the two groups. One study showed that supplementation of n-3 PUFA to obese patients revealed a significant reduction in the amount and percentage of abdominal fat in obese individuals and an increase in MoCA over time (Salman et al 2022 ). In a prospective cohort study by Liu found that α-linolenic acid (ALA) intake was negatively associated with weight gain (Liu et al 2018 ).…”
Section: Discussionmentioning
confidence: 99%